2004
DOI: 10.1182/blood-2004-06-2136
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Plasmodium falciparum to invade Southeast Asian ovalocytes varies between parasite lines

Abstract: IntroductionInvasion of host red blood cells (RBCs) by the merozoite is a pivotal step in the life cycle of the malaria parasite Plasmodium falciparum and a clear target for vaccine development. The process of invasion is complex and involves multiple ligand-receptor interactions that are still poorly understood. Additional complexity of this process comes from the heterogeneity among P falciparum lines in the use of particular receptors, as demonstrated by experiments with enzyme-treated and mutant RBCs. 1,2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 45 publications
5
51
0
Order By: Relevance
“…3,12,15 Earlier studies have showed reduced invasion or growth rates of P. falciparum in RBC from donors carrying SAO and GYPCDex3 . 13,14 The ability of P. falciparum to use different invasion pathways, redundancy in the erythrocyte invasion ligands used by P. falciparum , 29 and the earlier observation that only one of four EBA140/BAEBL variants (VSTK) failed to bind to Gerbich-negative erythrocytes, 30 could explain why the expected partial abrogation of the EBA140/BAEBL-GYPC invasion pathway by GYPCDex3 was observed to have little effect on infection rates or parasitemias in vivo . Whereas results from in vitro studies suggest that only a subset of parasite variants can invade SAO RBCs, those that can invade, do so efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,12,15 Earlier studies have showed reduced invasion or growth rates of P. falciparum in RBC from donors carrying SAO and GYPCDex3 . 13,14 The ability of P. falciparum to use different invasion pathways, redundancy in the erythrocyte invasion ligands used by P. falciparum , 29 and the earlier observation that only one of four EBA140/BAEBL variants (VSTK) failed to bind to Gerbich-negative erythrocytes, 30 could explain why the expected partial abrogation of the EBA140/BAEBL-GYPC invasion pathway by GYPCDex3 was observed to have little effect on infection rates or parasitemias in vivo . Whereas results from in vitro studies suggest that only a subset of parasite variants can invade SAO RBCs, those that can invade, do so efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 However, cross-sectional and case-control studies have so far not found any significant associations between SAO or GYPC genotypes and prevalence or density of P. falciparum infections. 3,12,15 To date, no longitudinal studies, which are less prone to bias and confounding factors, have been performed on either polymorphism and no studies investigating the role of GYPCDex3 and symptomatic malaria have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of alternative members of these families, possibly with different functional abilities, has the potential to mediate adaptation to changes in host metabolic/nutritional conditions, changes in temperature associated to febrile episodes, or host genetic polymorphism in erythrocyte receptors, respectively, which are probably the major fluctuating environmental conditions that P. falciparum asexual stages face beyond immune pressure (Merrick and Duraisingh 2010). Importantly, two of the transcriptionally different parasite lines characterized in this study differ in their ability to use alternative invasion pathways or to invade erythrocytes with the cerebral malaria-protective mutation SAO (Cortés et al 2004), and here we provide evidence that some of the parasite lines also differ in their sensitivity to heat-shock. Also supporting the idea that variant expression can modulate fitness and hence permit adaptation upon challenge, switches in the expression of clag3 genes were recently shown to result in altered sensitivity to chemical inhibitors (Nguitragool et al 2011) and may determine changes in solute permeability.…”
Section: Org Downloaded Frommentioning
confidence: 99%
“…3D7 stocks 3D7-A and 3D7-B, and 3D7-A subclones have also been described before (Cortés et al 2004(Cortés et al , 2007Cortés 2005). HB3A and HB3B are stocks of the same HB3 clonal parasite line obtained before (HB3A) or after (HB3B) mosquito and chimpanzee passage (Walliker et al 1987), kindly provided by O. Kaneko (Nagasaki University, Japan).…”
Section: Methods Parasitesmentioning
confidence: 99%
See 1 more Smart Citation